The Rate of Torque Development: A Unique, Non-invasive Indicator of Eccentric-induced Muscle Damage? - Jenkins, N. D. M.; Housh, T. J.; Traylor, D. A.; Cochrane, K. C.; Bergstrom, H. C.; Lewis, R. W.; Schmidt, R. J.; Johnson, G. O.; Cramer, J. T. (International Journal of Sports Medicine, 2014)
This study examined the time courses of recovery for isometric peak torque and rate of torque development (RTD) after eccentric-induced muscle damage. 18 men completed 6 sets of 10 maximal eccentric isokinetic muscle actions at 30° · s−1. Peak torque, peak RTD and RTD at 10 (RTD10), 50 (RTD50), 100 (RTD100) and 200 ms (RTD200), serum creatine kinase and lactate dehydrogenase were measured before (PRE), immediately after (POST), 24, 48 and 72 h after eccentric exercise. Creatine kinase and lactate dehydrogenase increased from 139 to 6 457 and from 116 to 199 IU · L−1 from PRE to 72 h, respectively. Peak torque and all RTDs decreased at POST. Peak torque and RTD200 remained lower than PRE through 72 h. Peak RTD remained lower than PRE through 48 h, but was not different from PRE at 72 h. RTD10 and RTD100 were lower than PRE through 24 h, but were not different from PRE at 48 and 72 h. RTD50 decreased at POST, but was not different from PRE at 24 h. Early phase RTDs recovered more quickly than PT and RTD200. Early phase RTDs may reflect neural mechanisms underlying eccentric-induced force decrements, while late RTDs may describe the same physiological mechanisms as PT.
Keywords: delayed onset muscle soreness; recovery; muscle strength; rapid torque-time curve; rate of force development